2013
DOI: 10.19030/ajbe.v6i3.7813
|View full text |Cite
|
Sign up to set email alerts
|

Online Course Evaluations Response Rates

Abstract: This paper studies the reasons for low response rates in online evaluations. Survey data are collected from the students to understand factors that might affect student participation in the course evaluation process. When course evaluations were opened to the student body, an email announcement was sent to all students, and a reminder email was sent a week later. Our study showed that participation rates increased not only when emails were sent, but also when faculty used in-class time to emphasize the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…Despite being optional, a third of all participants completed and sought to engage with the e-Learning platform for pain education, with those who engaged reported many of the beneficial attributes of e-Learning approaches. For those who did not participate, there was a sense of not seeing value, having the time, or the interest in using the platform, alongside experiencing issues with technology; similar experiences have been reported elsewhere [39]. Perceived usefulness of e-Learning can have a strong impact on students' e-Learning intention [40].…”
Section: Plos Onementioning
confidence: 82%
“…Despite being optional, a third of all participants completed and sought to engage with the e-Learning platform for pain education, with those who engaged reported many of the beneficial attributes of e-Learning approaches. For those who did not participate, there was a sense of not seeing value, having the time, or the interest in using the platform, alongside experiencing issues with technology; similar experiences have been reported elsewhere [39]. Perceived usefulness of e-Learning can have a strong impact on students' e-Learning intention [40].…”
Section: Plos Onementioning
confidence: 82%
“…However, in most cases, students are allowed to complete the evaluations voluntarily anytime during an announced timeframe. As a result, one study noted that the average online response rate is 23% less than the in-class collection response rate (Guder & Malliaris, 2013). Unfortunately, academicians have noted that biases exist between those who complete the evaluations and those who do not.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, this study explores nonresponse bias in online student evaluations. Low participation, or nonresponse, to online student evaluation of teaching (SET) is a major shortcoming of the technology (Guder & Malliaris, 2013). Nonresponse bias is defined as, "Error that results from a systematic difference between those who do and those who do not respond to a measurement instrument" (McDaniel & Gates, 2012, p. 156).…”
mentioning
confidence: 99%
“…Based on interviews with staff from three tertiary institutions in New Zealand, Stein et al (2013) reported that many lecturers view course evaluations as a popularity contest and therefore do not take the results seriously. Quantitative student evaluations are also plagued by lower response rates when compared with qualitative methods (Dommeyer et al 2002), making non-response error a common characteristic (Guder and Malliaris 2013).…”
Section: Literature Reviewmentioning
confidence: 99%